Effect on nutritional, sensory, textural and microbiological properties of low‐fat yoghurt supplemented with Jerusalem artichoke powder. (25th April 2017) - Guo, Xiulan; Xie, Zhenjian; Wang, Guoze; Zou, Qiang; Tang, Renyong
Abstract : The effect of supplementing two types of Jerusalem artichoke powder (JAP) with three different concentrations on the properties of low‐fat (LF) yoghurt was investigated. The results indicated that supplementation with JAPs improved the yoghurt's nutritional value, sensory score and microbial counts, while also ameliorating the syneresis, firmness and adhesiveness that was increased by the LF nature of the yoghurt. Although yoghurts with freeze‐dried (FD) JAP had higher viable counts of probiotics compared with oven‐dried (OD) JAP, the higher firmness and adhesiveness of yoghurts with the added FD JAP were undesirable. The yoghurt supplemented with 4% OD JAP had similar textural property and sensory scores to the full‐fat control. Therefore, OD JAP may be recommended based on its properties and low cost; 4% OD JAP could function as a nutritious prebiotic ingredient and fat replacer in LF yoghurt.